OpenPhi: an interface to access Philips iSyntax whole slide images for computational pathology - Mulliqi Nita; Kartasalo Kimmo; Olsson Henrik; Ji Xiaoyi; Egevad Lars; Eklund Martin; Ruusuvuori Pekka (OXFORD UNIV PRESS, 2022)
Digital pathology enables applying computational methods, such as deep learning, in pathology for improved diagnostics and prognostics, but lack of interoperability between whole slide image formats of different scanner vendors is a challenge for algorithm developers. We present OpenPhi-Open PatHology Interface, an Application Programming Interface for seamless access to the iSyntax format used by the Philips Ultra Fast Scanner, the first digital pathology scanner approved by the United States Food and Drug Administration. OpenPhi is extensible and easily interfaced with existing vendor-neutral applications.